The battle brawlers - West, Tracey, 1965- (New York : Scholastic, 2009)
As strange cards began to fall from the sky, kids all over the world discover that the cards are more than just a game-- they correspond to a world called Vestroia where a fierce battle is raging-- a battle that could destroy both Vestroia and the human world.
"Includes special character guide"--p. [1] of cover.
Keywords: Imaginary places -- Juvenile fiction; Good and evil -- Juvenile fiction; Imaginary places -- Fiction